Unravelling the regulating role of stacking pattern on the tunable dipole, mechanical behavior and carrier mobility for asymmetric Janus SnSSe bilayer. (December 2022) - Bai, Shulin; Ma, Yuxin; Wu, Mengxiu; Zhang, Jingyi; Luo, Dongming; Wan, Da; Tang, Shuwei
Abstract: Recently, Janus two-dimensional (2D) materials have attracted considerable interest because of the novel physical properties in view of reducing dimensionality and breaking reflection symmetry. With the help of first-principles calculations, the structural and mechanical, electronic structure and vertical dipole, and carrier mobility of SnSSe bilayer with different stacking patterns were comprehensively evaluated in this study. The calculations of binding energy and elastic constants demonstrate the experimental feasibility of SnSSe bilayer configurations with different stacking patterns. The bandgaps of SnSSe bilayer configurations can be regulated in the range of ~ 0.50 to ~ 0.75 eV due to the diversity of stacking patterns. Non-zero dipole moments induced built-in electric fields are found in SSnSe/SSnSe configurations, which unravels the dependence of the dipole moments on thickness and different stacking patterns. Additionally, the calculated carrier mobilities of SnSSe bilayer exhibits anisotropy and stacking pattern dependence, and the electron mobility can reach up to ~ 8513.63 cm 2 /V·s along the y -direction. Our present work would not only provide fundamental understanding of stacking dependence of dipole moment, mechanical behavior, and carrier mobility on asymmetric SnSSe bilayer, but also shed some light on the theoretical design of Janus SnSSe material within electronic, optoelectronic and thermoelectric applications. Graphical Abstract: ga1 Highlights: The SnSSe bilayer exhibits considerable stacking pattern dependence in physical properties. Non-zero dipole moments induced built-in electric fields are found in SSnSe/SSnSe configurations. The carrier mobility of SnSSe bilayer exhibits anisotropy in all configurations.